Estimating Yield and Economic Losses Induced by Ozone Exposure in South China Based on Full-Coverage Surface Ozone Reanalysis Data and High-Resolution Rice Maps - Jie Pei; Pengyu Liu; Huajun Fang; Xinyu Gao; Baihong Pan; Haolin Li; Han Guo; Feng Zhang (Agriculture, 2023)
Surface ozone (O3) pollution is an emerging environmental abiotic stress that poses substantial risks to crop yield losses and food security worldwide, and especially in China. However, the O3-induced detrimental effects on double-season rice have rarely been investigated at large scales and over relatively long temporal spans. In this study, we estimated the crop production reductions and associated economic losses for double-season rice across southern China during 2013–2019, using a high spatial resolution surface ozone reanalysis dataset and rice distribution maps, and county-level production data, in combination with a locally derived exposure-response function for rice. Results show that AOT40 (cumulative hourly O3 exposure above 40 ppb) presented generally increasing trends over growing seasons in 2013–2019, spanning from 4.0 to 7.1 ppm h and 6.1 to 10.5 ppm h for double-early rice and double-late rice, respectively. Moreover, O3-induced relative yield losses ranged from 4.0% to 6.6% for double-early rice and 6.3% to 11.1% for double-late rice. Over the seven years, ambient O3 exposure resulted in crop production losses of 1951.5 × 104 tons and economic losses of 8,081.03 million USD in total. To combat the O3-induced agricultural risks, measures such as stringent precursors emission reductions and breeding O3-resistant cultivars should be continuously implemented in the future.